Correction: Advancing inclusive research calculator for oncology disease areas: A resource to support the development of enrollment targets in diversity action plans for industry sponsors. - David J Press; Spencer L James; Bruno Jolain; Nicole Richie (PLoS ONE)
[This corrects the article DOI: 10.1371/journal.pone.0315283.].